Pick-up of Early Visual Information to Guide Kinetics and Kinematics within a Group of Highly Skilled Baseball Batters. Issue 2 (October 2014) - Müller, Sean; Lalović, Alex; Dempsey, Alasdair R.; Rosalie, Simon M.; Harbaugh, Allen G.
This pilot study integrated sport expertise and biomechanics methodologies within a baseball batting task. Purpose was to examine differences within a highly skilled group of baseball batters to use visual information to guide weight transfer and bat movements. One batter who played at Major League Baseball (MLB) level was compared to five batters who played at Australian Baseball League (ABL) level in a case-control design. Batters faced pitchers in a simulated competition and attempted to hit pitches, while vision was temporally occluded during ball flight or not occluded. Time of weight transfer (kinetics), as well as bat downswing initiation and duration (kinematics) from the point of ball release, were compared between the MLB batter and ABL batters. Results indicated that the MLB batter coordinated his striking pattern by completing his weight transfer earlier than the ABL batters. His bat downswing was also initiated earlier than some ABL batters, but there was no difference in duration of bat downswing between batters. All batters initiated bat downswing prior to completion of weight transfer. Understanding of motor expertise is furthered using a novel methodology.